Surgical smoke: A silent hazard in healthcare - Geetha Mani (Al Ameen Medical College, 2020)
Surgical smoke, known by various names such as surgical plume, smoke plume, diathermy plume and cautery smoke is the vaporization of substances, caused by thermal destruction of tissues using lasers and other energy-based electrosurgical devices [1]. Electro-surgical devices have become an integral part of surgery by virtue of their efficiency in improving hemostasis and minimizing duration of surgery [2]. Hence, the problem of surgical plume is here to stay